The use of a nasogastric tube to facilitate nasotracheal intubation: a randomised controlled trial - Chin Wai Lim; Seung-Kee Min; Chang‐Sung Kim; Jong-San Chang; Ji‐Eun Park; Jin-Young Hwang (2014)
Summary During nasotracheal intubation, the tracheal tube passes through either the upper or lower pathway in the nasal cavity, and it has been reported to be safer that the tracheal tube passes though the lower pathway, just below the inferior turbinate. We evaluated the use of a nasogastric tube as a guide to facilitate tracheal tube passage through the lower pathway, compared with the ‘conventional’ technique (blind insertion of the tracheal tube into the nasal cavity). A total of 60 adult patients undergoing oral and maxillofacial surgery were included in the study. In 20 out of 30 patients (66.7%) with the nasogastric tube‐guided technique, the tracheal tube passed through the lower pathway, compared with 8 out of 30 patients (26.7%) with the ‘conventional’ technique (p = 0.004). Use of the nasogastric tube‐guided technique reduced the incidence and severity of epistaxis (p = 0.027), improved navigability (p = 0.034) and required fewer manipulations (p = 0.001) than the ‘conventional’ technique.